A framework for continuation of digitalization in construction: a PLS-SEM approach - Bajpai, Avirag; Misra, Subhas C. (Engineering, construction, and architectural management, 2023)
PurposeIndian construction firms are falling behind in the use of digital technology in the workplace, and this study aims to give a framework and assess the role of enablers in the implementation and continuing digitalization of the Indian construction sector.Design/methodology/approachAn exploratory qualitative research technique is used in this article, and multiple detailed interviews and surveys are done with professionals from the industry and academia. To conclude the significance and relevance of the different constructs and indicators, the partial least square-structural equation modeling (PLS-SEM) approach is used.FindingsBarriers are essential enablers for effective implementation, while success factors are important drivers for the successful continuance of digitalization in the construction sector. However, stakeholders' perceived benefit has a substantial role in both implementation and continuance.Research limitations/implicationsIn this research paper, the scope of this investigation for a generalized exploratory study is restricted to construction firms within India. Further, a rigorous longitudinal study may also be performed to examine the subjectivity of the responses in order to ensure digital continuation. This study identifies limited manifest indicators. Additional indications, however, may be included based on the other company's resources, structure and geographic location.Practical implicationsThe study's findings have two implications. In the beginning, it gives a direction to the construction sector by highlighting the framework in which implementation and continuance both should have to be executed, and this is the critical area for the successful continuance of digitalization in construction. Second, the research shows that the digitalization process is similar to the adoption of innovation, in which the deployment and persistent use of the new technology are important for facilitating the transformation.Originality/valueIn two respects, the study is distinctive. To begin, this is one of the limited efforts to comprehend digitalization from the Indian perspective. Second, the study reveals that the PLS-SEM approach can be effectively used in the developing subject of the construction digitalization concept.